Differences in the susceptibility of human tubular epithelial cells for infection with orthohantaviruses - Schreiber, Pamela; Friedrich, Ann-Kathrin; Gruber, Gefion; Nußhag, Christian; Boegelein, Lukas; Eßbauer, Sandra; Uhrig, Josephine; Zeier, Martin; Krautkrämer, Ellen (Viruses, 2023)
Diseases induced by infection with pathogenic orthohantaviruses are characterized by a pronounced organ-specific manifestation. Pathogenic Eurasian orthohantaviruses cause hemorrhagic fever with renal syndrome (HFRS) with often massive proteinuria. Therefore, the use of a relevant kidney cell culture would be favorable to analyze the underlying cellular mechanisms of orthohantavirus-induced acute kidney injury (AKI). We tested different human tubular epithelial cell lines for their suitability as an in vitro infection model. Permissiveness and replication kinetics of highly pathogenic Hantaan virus (HTNV) and non-/low-pathogenic Tula virus (TULV) were analyzed in tubular epithelial cell lines and compared to human primary tubular epithelial cells. Ana-lysis of the cell line HK-2 revealed the same results for viral replication, morphological and functional effects as observed for HTNV in primary cells. In contrast, the cell lines RPTEC/TERT1 and TH1 demonstrated only poor infection rates after inoculation with HTNV and are unusable as an infection model. While pathogenic HNTV infects primary tubular and HK-2 cells, non-/low-pathogenic TULV infects neither primary tubular cells nor the cell line HK-2. Our results show that permissiveness of renal cells varies between orthohantaviruses with differences in pathogenicity and that HK-2 cells demonstrate a suitable in vitro model to study viral tropism and pathogenesis of orthohantavirus-induced AKI.
Gesehen am 16.10.2023